Unveiling triple vulnerability among Mozambican female sex workers—Stigma, physical violence and sexual violence - Naira Luiz; Rachid Muleia; Ana Abecasis; Auria Banze; Denise Langa; Cynthia Semá Baltazar (PLoS ONE, 2025)
Background In the shadows of Mozambique’s urban landscape, an invisible struggle unfolds among its most vulnerable: Female Sex Workers (FSWSs). FSWs bear a disproportionate burden of violence as a consequence of the stigma surrounding their profession, as both stigma and violence create significant barriers to the progress of HIV elimination within this group by limiting their access to prevention and treatment services, discourages them from seeking help, while violence itself increases vulnerability to HIV. This study examines the patterns of stigma, physical and sexual violence, and HIV among FSWs. Methodology A secondary analysis was performed using data from a cross-sectional Bio-Behavioral Survey (BBS) conducted among FSW ≥15 and old, implemented between 2019–2020 in five urban areas. Respondent-driven sampling (RDS) was utilized to recruit participants. Aggregate weighted estimates were calculated for self-reported stigma, physical, and sexual violence. Associations between variables were assessed using chi-squared tests, and multivariate logistic regression was employed to identify factors associated with stigma, physical violence, and sexual violence. Results Among 2,567 FSWs surveyed, 24.7% reported experiencing stigma, while 52.3% and 37.9% reported physical and sexual violence, respectively, in the six months preceding the survey. The likelihood of experiencing stigma was over six times higher for FSWs who engaged with more than 7 clients (AOR = 6.1; p <0.001). Drug use was associated with a twofold increase in the odds of physical violence (AOR = 2.3; p <0.001) and a nearly threefold increase in the odds of sexual violence (AOR = 2.7; p <0.001). HIV-positive FSWs were at increased risk for both physical violence (AOR = 1.2; p = 0.006) and sexual violence (AOR = 1.2; p = 0.031). Conclusion This study highlights the substantial burden of stigma and violence among FSWs in Mozambique’s urban areas. The findings underscore the urgent need for targeted interventions to reduce stigma, prevent violence, and protect the rights of FSWs. Addressing these issues is essential for achieving the goals of HIV prevention and treatment in this vulnerable population.